Haematological, serum biochemical and anti‐oxidative enzymes responses of sutchi catfish (Pangasianodon hypophthalmus) against Aeromonas hydrophila using various carbon sources in biofloc system. (14th December 2021) - Nageswari, Ponpandy; Verma, Ajit Kumar; Gupta, Subodh; Jeyakumari, Annamalai; Mallikarjun Hittinahalli, Chandrakant
Abstract: A 90‐day experiment was conducted to study haematological, serum biochemical and anti‐oxidative enzymes responses of sutchi catfish ( Pangasianodon hypophthalmus ) fingerlings in biofloc system using various carbon sources. The experiment consisted of four treatments and control (clearwater) having three replicates using three hundred sutchi catfish fingerlings (6.40 ± 0.05 g) in 15 tanks (20 in 100 L). Various carbon sources viz . tapioca, sorghum, pearl millet, and finger millet were assigned as BFT‐T, BFT‐S, BFT‐PM and BFT‐FM, respectively. Post‐rearing, sutchi catfish were challenged with Aeromonas hydrophila (1 × 10 7 cfu/ml), and blood and serum parameters were analysed. During pre‐challenge condition, significantly ( p < 0.05) higher haemoglobin concentration (7.69 ± 0.13 g/dl), total erythrocytes count (1.62 ± 0.02 10 6 cells/mm 3 ), total leucocytes count (137.34 ± 4.37 10 3 cells/mm 3 ), packed cell volume (23.93 ± 1.84%) and mean corpuscular volume (142.33 ± 6.80 fL) were observed in BFT‐FM as compared to control. The mean corpuscular haemoglobin and mean corpuscular haemoglobin concentration did not differ significantly among the treatments. The serum biochemical parameters were significantly higher in BFT‐FM compared to other treatments. The serum glucose (59.44 ± 2.04 mg/dl) and cortisol (50.82 ± 2.21 ng/ml) were significantly lower in BFT‐FM than other treatments and control. Serum superoxide dismutase and catalase values increased significantly in biofloc groups when compared with control. The haematological and biochemical values did not differ significantly between the pre‐ and post‐challenge conditions, and stimulated immune response was observed in sutchi catfish against A. hydrophila . The results reveal that finger millet‐based biofloc application acts as an immunostimulator; and thereby, reducing the stress and improving haematology and biochemical status of P. hypophthalmus fingerlings.